Workshop dan Pendampingan Bidang Pajak dan Akuntansi bagi Amal Usaha Muhammadiyah (AUM) Se-Kabupaten Tuban - muhammad aufa; Syaiful Syaiful; Nyimas Wardatul Afiqoh (Jurnal Pengabdian Manajemen, 2023)
Persyarikatan Muhammadiyah already has a large number of business charities. As an organization that echoes the spirit of progress, Muhammadiyah continues to improve in organizational management to realize good organizational governance. This service is part of efforts to realize good governance, especially in the field of financial management. This dedication partner is Muhammdiyah's charitable efforts in the fields of Education and Health in Tuban district. The form of activity is workshops and assistance in the field of tax and accounting. The initial workshop and mentoring activities were carried out by controlling business charity status (AUM) for the purpose of issuing Business Identification Numbers (NIB). Assistance is carried out after AUM has a NPWP, Financial Statements and NIB.